(3efGbod GdoqOQQ hefGHoJ GdnqRgQs - (3CHh GdhdjO ESeGYjd Hf eMeO GdETjjdj GHf QCS ZfeI, GHf QCS ZfeI,J (B620 (3g` s ((3GdMGL Hf CHj YjGO s)
(3ChdgG (B:s
(3GdMeO ddg GdeJWhd HBdBFg GdeJaVd HfYeGFg GdeJaQO HedchJg ahb SeGFg GdYGOd Hjf LejY GdNdb ai Mceg hbVGAg s
(3BNQgG (B:s
(3GfJgi GdOjhGf GdeHGQc HMeO Gddg hMSf Yhfgq s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B376s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs